A heterogeneous integrated self-powered IoT system of an LiNbO3 device and CMOS readout circuit - Wang, Xiuyu; Kang, Min; Zhao, Yang; Su, Yue; Zhang, Xu; Mao, Xurui (Frontiers in Physics, 2022)
Self-powered IoT system with high integration, robust performance, and adaptability to complex environments are one of the current research hotspots. Piezoelectric materials have been widely used in pressure sensing and energy harvesting due to their stable output electrical properties. In this paper, a heterogeneous integrated self-powered IoT system based on lithium niobate (LiNbO3) piezoelectric device and CMOS readout circuit is proposed. The piezoelectric sensor is fabricated by depositing electrodes on the surface of 36°Y-cut LiNbO3 piezoelectric material. The sensitivity of the fabricated sensor is 17.5 mV/kPa. Based on CSMC 0.18 μm BCD process, a ring voltage-controlled oscillator (VCO) based on current starvation delay element is designed as a wireless data transmission unit. The oscillator has two tuning terminals, which can realize frequency alignment and voltage threshold judgment, respectively. Through photolithography, wire bonding technology, etc., the heterogeneous integration of Si-based chip and LiNbO3 piezoelectric device is realized. The experimental results show that under the 1.8 V supply voltage, the oscillation frequency of the chip increases with the increase of the control terminal voltage, which provides an idea for solving the energy supply problem of IoT system. This system has great application potential in the field of self-powered sensing.